Research on Recovery Mechanism and Process of Waste Thermosetting Phenolic Resins Based on Mechanochemical Method - Jian Hu; Huifang Dong; Shouxu Song (Advances in Materials Science and Engineering)
The present study analyzed the recovery mechanism of the thermosetting phenolic resin waste, optimizing the recovery process parameters, based on the mechanochemical recovery method. The physical and chemical structure of the ultrapulverized phenolic resin powder was characterized by the low-field NMR (nuclear magnetic resonance), IR (infrared spectroscopy), and SEM (scanning electron microscopy). The recovery process parameters were designed by using the response surface analysis method, and the multiple quadratic regression model was established and the multiobjective process parameter was optimized. The results show that the body network structure of the material is destroyed during the crushing process. The intensity of the internal cross-linking signal is reduced and tends to be stable at about 60%, when the particle size exceeds 120 mesh. The cross-linking bonds methylene (-CH2-) in the main chain of the molecular chain and the C-O bond in the methylol group on the branch are broken. The tensile strength of the recycled sheet made of the phenolic resin powder is 8.27 MPa, and the bending strength is 17.76 Mpa through the mechanical properties test. The influences on the change rate of the cross-linking signal intensity and the yield of the recycled powder are in the following order: rotation speed, feed size, time, and feed volume. The best recovery parameters are as follows: rotation speed of 2820 r/min, time of 80 min, feed particle diameter of 0.43 mm, and feed volume of 60 g.